2021
DOI: 10.35445/alishlah.v13i3.639
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Online Learning Media in the Covid-19 Pandemic

Abstract: This qualitative research aims to obtain an overview of the implementation of online learning in the Covid-19 Pandemic. In general, the implementation of online learning during the Covid-19 pandemic positively impacts the continuity of education in Indonesia. This research method is obtained from online observations and Scoping reviews. Literature is obtained from various databases such as Google Scholar, Scopus, Web of Science, Crossref Search. Furthermore, the literature was mapped in several parts so that 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…More than that, the role of the community, in this case the parents should not be ignored. As stated by Abduloh et al (2021) that the use of technological devices as a means of online learning also requires supervision from the parents of students.…”
Section: Figure 4 Evaluation Of Online Learning According To Respondentsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than that, the role of the community, in this case the parents should not be ignored. As stated by Abduloh et al (2021) that the use of technological devices as a means of online learning also requires supervision from the parents of students.…”
Section: Figure 4 Evaluation Of Online Learning According To Respondentsmentioning
confidence: 99%
“…However, it is different from Nastiti & Hayati (2020), the research results found that lecturers and students at Banjarmasin City universities already have good readiness in facing online lectures, because generally they have been able to use digital learning tools well. Likewise with Abduloh et al (2021) found that online learning during the Covid-19 pandemic was considered effective to replace conventional learning systems, although several factors related to the implementation of online learning must still be considered. On the other hand, the research results of Harunasari, Dwigustini, Halim, & Susillawati (2021) found that more than 50% of students in Indonesia stated that online learning during the Covid-19 pandemic was considered useful, but it was not easy to use the technology.…”
Section: Introductionmentioning
confidence: 99%
“…Several aspects of human life have been dramatically altered by the Covid 19 virus, which has spread across the world (Herliandry et al, 2020;Rahman & Subiyantoro, 2021;Musliadi et al, 2021). This has led to a new policy issued by the Indonesian government, namely the implementation of physical distancing in various fields of human life, especially in the area of education (Adham & Mahmudah, 2021;Rifqi, 2021;Muhammadiah & Susilo, 2021;Ramdani et al, 2021). Through this policy, of course, has an impact on the patterns and styles of learning carried out by educational institutions, communication systems, services, and so on (Mustajab & Fawa'iedah, 2020;Maman et al, Taqwa, Sumardin Raupu / Website-Based Academic Service Development with ADDIE Design in Higher Education 2021), which must be this is done online, so inevitably you have to use information technology tools (Suwidiyanti & Anshori, 2021;Mushfi et al, 2021;Zamroni & Qatrunnada, 2021) .…”
Section: Introductionmentioning
confidence: 99%